2003
DOI: 10.1016/j.jacc.2003.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and angiographic correlates and outcomes of suboptimal coronary flow inpatients with acute myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: Final TIMI < or =2 flow, although uncommon after primary PCI, was strongly associated with hospital and one-year adverse events. The clustering of final TIMI < or =2 flow in high-risk groups may partially explain the poor prognosis of these patients. Awareness of these risk factors may be useful to clinicians to triage and treat patients undergoing primary PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(102 citation statements)
references
References 36 publications
7
90
2
3
Order By: Relevance
“…The results were consistent with previous studies evaluated predictors of TIMI 2 in patients with acute ST segment elevation myocardial infarction (STEMI) undergoing primary PCI. 6,15 Our study also demonstrated that statin was also an independent predictor for the no-reflow, which was consistent with the report of Iwakura. 16…”
Section: Predictors Of No-reflowsupporting
confidence: 91%
See 1 more Smart Citation
“…The results were consistent with previous studies evaluated predictors of TIMI 2 in patients with acute ST segment elevation myocardial infarction (STEMI) undergoing primary PCI. 6,15 Our study also demonstrated that statin was also an independent predictor for the no-reflow, which was consistent with the report of Iwakura. 16…”
Section: Predictors Of No-reflowsupporting
confidence: 91%
“…However, previous studies have identified greater size of the risk area is closely related to the no-reflow phenomenon. 15 The doses of ACEI in the study may be lower than the maximal recommended doses. This may lead to an underestimation of the effect of ACEI on noreflow.…”
Section: Limitation Of the Studymentioning
confidence: 98%
“…Previous studies identified DM, age, hypertension, and pre-PCI TIMI flow as the independent predictors for suboptimal coronary flow. [33][34][35] In this study, postprocedural suboptimal coronary flow was diagnosed by coronary angiography and we found that LVEF, HDL cholesterol, Hb in STEMI and culprit vessel type, and the extent of multivessel disease in NSTEMI were the independent predictors for postprocedural suboptimal coronary flow after PCI.…”
Section: Discussionmentioning
confidence: 61%
“…The success rate of achieving the postprocedural TIMI 3 flow and related patient characteristics in the present study conform to other studies: patients with postprocedural TIMI <3 flow were older, more commonly women, diabetics, with more frequent initial hemodynamic instability (Table 1) (ref. 9,16 ). Current smoking was associated with lower incidence of postprocedural TIMI <3 flow, which was observed previously in studies with thrombolysis in AMI (ref.…”
Section: Timi-3 Flow As An Outcome Predictormentioning
confidence: 99%